Analisis Faktor Risiko Kejadian Preeklampsia Berat di Kabupaten Mesuji - Irawati, Candra; Budiati, Endang; Rahayu, Dewi (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT According to WHO (2021), around 295,000 women die, the most common causes being bleeding, high blood pressure, infection and unsafe abortion. The aim of this research is to find out the risk factors for the occurrence of severe preeclampsia in Mesuji Regency in 2023. This type of quantitative research with a case control approach design. The study population was all pregnant women at 22 weeks' gestation with a total of 2,710 mothers, with a total of 105 research respondents. The results of the bivariate analysis stated that there was a relationship between completeness of ANC visits p-value 0.000, history of hypertension p-value 0.023, nutritional status p-value 0.000, obesity p-value 0.027 and family support p-value 0.016 with the incidence of severe preeclampsia. There is no relationship between maternal age and a p-value of 0.599 with the incidence of severe preeclampsia. The results of the multivariate analysis showed that the mother's nutritional status was the dominant factor associated with the incidence of severe preeclampsia with a p-value of 0.000 and an OR (odds ratio) of 8.588. Suggestions for the community health centre to increase mentoring and education on the importance of intake patterns and improving the nutrition of pregnant women, and it is hoped that the local government can bridge the collaboration between various sectors and interested stakeholders in efforts to improve nutrition and strategies for receiving health services for all people, especially those with low accessibility in Mesuji Regency Keywords: Risk Factors, Severe Preeclampsia  ABSTRAK Preeclampsia merupakan penyebab umum kematian ibu paa masa kehamilan dan persalinan. Menurut WHO (2021), sekitar 295.000 wanita meninggal, penyebab paling umum yaitu perdarahan, tekanan darah tinggi, infeksi dan aborsi tidak aman. Penelitian ini dilakukan untuk mengetahui faktor risiko kejadian preeclampsia berat di Kabupaten Mesuji tahun 2023. Jenis penelitian kuantitatif dengan desain pendekatan case control. Populasi penelitian yaitu seluruh ibu hamil usia kehamilan 22 minggu dengan jumlah 2.710 ibu, dengan total responden penelitian sejumlah 105 orang. Berdasarkan penelitian, diketahui bahwa ada hubungan kelengkapan kunjungan ANC p-value 0,000, riwayat hipertensi p-value 0,023, status gizi p-value 0,000, obesitas p-value 0,027 dan dukungan keluarga p-value 0,016 dengan kejadian preeclampsia berat. Tidak ada hubungan umur ibu dengan nilai p-value 0,599 dengan kejadian preeclampsia berat. Variabel status gizi ibu menjadi faktor dominan yang berhubungan dengan kejadian preeclampsia berat dengan p-value 0,000 dan OR (odd ratio) 8,588. Saran bagi puskesmas meningkatkan pendampingan dan edukasi pentingnya pola asupa dan perbaikan gizi ibu hamil, serta diharapkan pemerintah daerah dapat menjembatani terjalinnya kolaborasi antar berbagai sektor dan stakeholder yang berkepentingan dalam upaya perbaikan gizi dan strategi penerimaan layanan kesehatan kepada seluruh masyarakat terutama dengan aksesibilitas rendah di Kabupaten Mesuji. Kata Kunci: Faktor Risiko, Preeklampsia Berat